"Conservation" as a Catalyst for Conflict: Considering Stakeholder Understanding in Policy Making1. Issue 3 (22nd May 2013) - Crow, Deserai Anderson; Baysha, Olga
Abstract Stakeholder negotiation processes are increasingly used in environmental management, but are often difficult due to values differences among stakeholders. These values can be reflected in the language used by stakeholders, which may lead to conflict in negotiation processes. This study investigated whether there are widespread differences among Colorado water stakeholders in how they define the term "conservation, " a key value and policy term, and whether this leads to conflict in negotiations. Using multiple methods in a cross‐sectional case study, use of the term and possible policy implications were analyzed. Stakeholder respondents in this study who had experienced difficulty in water negotiations also perceived a higher degree of miscommunication in their negotiations. The most important finding presented here suggests that clarity of language and transparent discussion of key value‐representative terms may aid in stakeholder negotiations, and that minority stakeholders may be more aware of values and language differences than their majority counterparts.